Sintaksis frasa nama bahasa Kensiu (Jurnal Bahasa, 2009)
Austro-Asiatic languages in Malaysia are considered as a moribund language as these languages are facing extinction. Hence, this writing will focus on one of the moribund languages in Peninsular Malaysia, namey Kensiu language which is fast becoming extinct. This language is spoken by Kensiu people in Baling, Kedah. The number of its speakers is less than 200 people. However; this writing will only discuss on the noun phrase (NP) of Kensiu language. The analysis on the noun phrase of Kensiu language in article is divided into two aspects: descriptive and syntactic aspects. The descriptive analysis explain the noun phrase of the Kensiu language and all the sequences that form the noun phrase. Further, guided with the descriptive analusis, this writer will discuss the X'syntactic structure of the Kensiu noun phrase by using Government and Binding Theory Framework (Chomsky, 1986). From the outcome of this analysis, this writer will demonstrate the adjunction structure ofthe Kensiu's NP.